1985
DOI: 10.1111/j.1151-2916.1985.tb16156.x
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Fatigue Properties of Optical Glass Fibers Containing Microindentation Flaws

Abstract: The inert strength and dynamic fatigue properties of fusedsilica optical fibers are studied using subthreshold indentation flaws, i.e., flaws without radial cracks. These subthreshold properties differ from those obtained in comparative tests on silica rods containing postthreshold indentation flaws in three major respects: (I) the inert strengths are significantly higher than predicted by extrapolation of the postthreshold data;(2) the slopes of the dynamic fatigue plots are likewise greater, indicating a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Baikova, Pukh and Talalakin (1974) and Aslanova et al (1982) present data for indentation on HF-etched silica surfaces. Their data roughly agree with those of Dabbs and Lawn (1985) and Jakus et al (1988) but it is not clear what test environment they used.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Baikova, Pukh and Talalakin (1974) and Aslanova et al (1982) present data for indentation on HF-etched silica surfaces. Their data roughly agree with those of Dabbs and Lawn (1985) and Jakus et al (1988) but it is not clear what test environment they used.…”
supporting
confidence: 89%
“…This technique is particularly useful since the residual strength can be controlled over a wide range by varying the indentation load. Dabbs and Lawn (1985) observed that, while radial cracks form at the indentation comers at high loads, radial cracks are not formed below some threshold load. They found that the residual strength of subthreshold and post-threshold indents do not follow the same trends with the presence of radial cracks causing post-threshold indents to be discontinuously weaker than subthreshold indents.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…in high strength specimens failure is initiation controlled; in low strength specimens failure results from crack "pop-in" followed by subcritical crack growth (propagation controlled failure). 5 We observed that the results for subthreshold flaws measured in two point and four point bending do not form one continuous line. The results from the four point apparatus are calculated assuming small deflections of the fiber.…”
Section: Methodsmentioning
confidence: 73%
“…According to Dabbs and Lawn [6] values for n of about 20 and lower corresponds to damages made at sub threshold loads. Then, the calculated value for n indicates the indentations made in the fibers generate flaws into the glass surface in a post threshold regime.…”
Section: Discussionmentioning
confidence: 99%